Toward an organic Lebanon - Touma R.S. (The market for organic products in the Mediterranean region, 2003)
While organic agriculture has reached its peak level in terms of development around the world, it is still in its embryonic stage in Lebanon. De facto organic farming used to occur by default before the 60's. However, throughout the last four decades the intensive use of agro-chemicals became a must to increase yields. This double-edged sword lead to deterioration in the quality of produce as well as a break in the ecological balance. The last decade witnessed a lot of awareness to health and environmental issues and imported organic products found their place on the Lebanese supermarket shelves and in specialty shops. An increasing number of farmers started to adopt organic farming despite the fact that there is still no established certifying body since there are no national standards. Universities, NGOs and other institutions are making efforts to promote organic agriculture through research and implementation of pilot projects. They are further trying to develop the national standards. There are good prospects for promoting organic agriculture in Lebanon. The demand for healthy food in the local market is increasing and there is a great potential for export in view of the favorable climatic conditions and ecological diversity that Lebanon enjoys. However, there is a need for a comprehensive scheme to be initiated by researchers and NGOs with the indispensable facilitation by the Ministry of Agriculture and the adoption by the private sector.
Intensive Course in: Marketing of Organic Products, 2002/05/20-31, Izmir (Turkey)